2022
DOI: 10.3389/fbioe.2022.859927
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Encapsulation: Taking the Therapy of Mesenchymal Stem Cells and Their Derived Secretome to the Next Level

Abstract: Biomaterials have long been the focus of research and hydrogels are representatives thereof. Hydrogels have attracted much attention in the medical sciences, especially as a candidate drug-carrier. Mesenchymal stem cells (MSC) and MSC-derived secretome are a promising therapeutic method, owing to the intrinsic therapeutic properties thereof. The low cell retention and poor survival rate of MSCs make further research difficult, which is a problem that hydrogel encapsulation largely solved. In this review, safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Therefore, tissue engineering strategies for designing an effective biomaterial for vocal fold treatment have been highlighted to facilitate local healing and restore their native function 12 . An example is the use of mesenchymal stem cells (MSCs) or secretome encapsulation in hydrogel to promote native tissue regeneration and reduce the local immune system 13 . With that, current study serves as a preliminary study to develop a hydrogel which has potential for cell encapsulation in future work, in providing regenerative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tissue engineering strategies for designing an effective biomaterial for vocal fold treatment have been highlighted to facilitate local healing and restore their native function 12 . An example is the use of mesenchymal stem cells (MSCs) or secretome encapsulation in hydrogel to promote native tissue regeneration and reduce the local immune system 13 . With that, current study serves as a preliminary study to develop a hydrogel which has potential for cell encapsulation in future work, in providing regenerative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cell therapy, hydrogels provide clear advantages to conventional culture. Their biophysical characteristics can be easily adjusted, other external physical stimuli (such as cyclic stretch) can be applied, are used as bioinks for bioprinting, and can be used as vehicle facilitating MSCs engraftment and viability after transplantation [12,13,24]. This work reveals that L-HG is also an important source of bioactive proteins and derived vesicles that can modulate multiple cellular mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, hydrogel-encapsulated MSCs could further alleviate acute lung injury, increasing the expression of several growth factors and interleukin-10 [12]. In addition, hydrogel-encapsulated MSCs showed better cell survival and could increase their engraftment in the injured tissue [13]. Thus, biomechanical preconditioning of cultured MSCs in physiomimetic hydrogels is a promising strategy to improve cell therapy in future clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome limitations associated with 2D culture, 3D cell culture techniques have been developed in the last decades that aim to recapitulate aspects of in vivo microenvironment. Studies have shown that physiological functionalities and characteristics of MSCs can be maintained to a greater extent if cells are cultured in suitable 3D systems. The suitability of such systems is highly dependent on employed biomaterials and the associated biophysical properties, which ultimately affect adherence, proliferation, differentiation, and migration of MSCs. In this context, hydrogels have attracted attention in regenerative medicine due to their capacity to mimic aspects of the extracellular matrix (ECM) and thus provide a more in vivo -like microenvironment to the embedded cells during in vitro culture . Several types of synthetic and natural origin hydrogels, such as hyaluronic acid, alginate, collagen, gelatin, poly­(ethylene glycol), and poly­(lactic- co -glycolic acid) have been studied for cultivation of MSCs in 3D .…”
Section: Introductionmentioning
confidence: 99%
“… 18 20 In this context, hydrogels have attracted attention in regenerative medicine due to their capacity to mimic aspects of the extracellular matrix (ECM) and thus provide a more in vivo -like microenvironment to the embedded cells during in vitro culture. 21 Several types of synthetic and natural origin hydrogels, such as hyaluronic acid, alginate, collagen, gelatin, poly(ethylene glycol), and poly(lactic- co -glycolic acid) have been studied for cultivation of MSCs in 3D. 22 Hydrogels for biomedical applications are often associated with certain drawbacks, such as low mechanical stability, high variability, use of chemical cross-linking agents or irradiation and manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%